A comprehensive review of sweet potato (Ipomoea batatas [L.] Lam): Revisiting the associated health benefits. (September 2021) - Alam, Mohammad Khairul
Abstract: Background: Sweet potatoes ( Ipomoea batatas [L.] Lam) have become a trending research topic in recent years due to their special nutritional and functional properties. The bioactive carbohydrates, proteins, carotenoids, flavonoids, anthocyanins, phenolic acids and minerals are diverse nutrients present in the leaves and roots of sweet potato. Scope and approach: This review offers an update based on the latest literature on the nutritional value, phytochemical composition and health beneficial properties of sweet potato. In addition to the beneficial nutritional composition of sweet potatoes, a number of constituents capable of promoting health well-being and preventing lifestyle-related diseases are present in the sweet potatoes (roots and leaves). The findings of in vitro and in vivo research on the health benefits of sweet potato bioactives reported in the last decade have been collected and updated. Key findings and conclusions: A number of different health benefits, such as antioxidant, cardioprotective, anti-inflammatory, anti-cancer, anti-diabetic, antimicrobial, anti-obesity and prevention of vitamin A malnutrition have been reported due to the ingestion of different parts of sweet potato. Compositional analysis revealed the orange-fleshed sweet potato varieties are superior source of β-carotene while the purple-fleshed sweet potato varieties have the excellent levels of anthocyanins. Whereas, the white-fleshed sweet potato varieties nearly contain no β-carotene. The dietary intakes of sweat potatoes are strongly recommended for their undeniable health-promoting properties. They also offer potential application in food industries for novel value-added food products and products prepared with or from sweet potato are compiled. Graphical abstract: Image 1 Highlights: Health benefits, in vitro and in vivo, of sweet potato roots and leaves were presented. Orange-fleshed sweet potato varieties are superior source of β-carotene (pro-vitamin A). Purple-fleshed sweet potato varieties have the excellent levels of anthocyanins. Sweet potatoes could be utilized as potential material for novel products formulation.